Case Report: Local Cytokine Release Syndrome in an Acute Lymphoblastic Leukemia Patient After Treatment With Chimeric Antigen Receptor T-Cell Therapy: A Possible Model, Literature Review and Perspective - Luan, Chengxin; Zhou, Junjie; Wang, Haixia; Ma, Xiaoyu; Long, Zhangbiao; Cheng, Xin; Chen, Xiaowen; Huang, Zhenqi; Zhang, Dagan; Xia, Ruixiang; Ge, Jian (Frontiers in Immunology, 2021)
Chimeric antigen receptor T (CAR-T) cell therapy has achieved remarkable clinical efficacy in treatment of many malignancies especially for B-cell hematologic malignancies. However, the application of CAR-T cells is hampered by potentially adverse events, of which cytokine release syndrome (CRS) is one of the severest and the most studied. Local cytokine-release syndrome (L-CRS) at particular parts of the body has been reported once in a while in B-cell lymphoma or other compartmental tumors. The underlying mechanism of L-CRS is not well understood and the existing reports attempting to illustrate it only involve compartmental tumors, some of which even indicated L-CRS only happens in compartmental tumors. Acute lymphoblastic leukemia (ALL) is systemic and our center treated a B-cell ALL patient who exhibited life threatening dyspnea, L-CRS was under suspicion and the patient was successfully rescued with treatment algorithm of CRS. The case is the firstly reported L-CRS related to systemic malignancies and we tentatively propose a model to illustrate the occurrence and development of L-CRS of systemic malignancies inspired by the case and literature, with emphasis on the new recognition of L-CRS.